2015
DOI: 10.1039/c5dt02480c
|View full text |Cite
|
Sign up to set email alerts
|

Induction of E/Z isomerization in a pendant metal-bound azobenzene: a synthetic, spectroscopic and theoretical study

Abstract: Re(CO)3 conjugates 1 and 2 that incorporate azobenzenes can be readily generated via one-pot reactions using Schiff base reaction forming conditions. Excitation of the MLCT bands in 1 and 2 results in isomerization of the azobenzene moiety, and this process has been investigated via time-resolved photophysics and TDDFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A previously reported approach for the combinatorial synthesis of anticancer ruthenium-arene complexes exploited the metal-templated condensation of anilines with picolinaldehydes to yield new compounds bearing pyridylimine ligands. , Based on the promising anticancer activities of rhenium­(I) tricarbonyl complexes, we aimed to adapt this condensation chemistry for the generation of a diverse library of these compounds. The feasibility of this strategy was bolstered by previous studies that have demonstrated that Re­(CO) 5 Cl acts as an appropriate template for aniline-picolinaldehyde condensation chemistry to afford rhenium­(I) tricarbonyl complexes bearing pyridylimine ligands. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously reported approach for the combinatorial synthesis of anticancer ruthenium-arene complexes exploited the metal-templated condensation of anilines with picolinaldehydes to yield new compounds bearing pyridylimine ligands. , Based on the promising anticancer activities of rhenium­(I) tricarbonyl complexes, we aimed to adapt this condensation chemistry for the generation of a diverse library of these compounds. The feasibility of this strategy was bolstered by previous studies that have demonstrated that Re­(CO) 5 Cl acts as an appropriate template for aniline-picolinaldehyde condensation chemistry to afford rhenium­(I) tricarbonyl complexes bearing pyridylimine ligands. …”
Section: Resultsmentioning
confidence: 99%
“…All reagents were purchased from commercial vendors. The lead rhenium complexes and the corresponding free ligands were synthesized according to literature methods with slight modifications. , All reactions were performed under ambient atmospheric conditions without any efforts to exclude oxygen or water. Solvents used were of ACS grade or higher.…”
Section: Methodsmentioning
confidence: 99%
“…Re(CO) 3 diimine complexes exhibit metal-to-ligand charge-transfer (MLCT) transitions that show much higher molar absorbtivity (>5 times higher for 4 and 5 , and ~20 times higher for 6 and 7 ). The molar absorptivities of 4 and 5 were comparable to those observed in mono-rhenium tricarbonyl Schiffs base compounds with absorptivities around 3,000–4,000 M −1 cm −1 [44,45]. Complexes ( 6 and 7 ) show stronger absorbtivities in the range of 7,000–8,000 M −1 cm −1 , about twice as much as those of monomeric Re(CO) 3 Schiff’s base complexes, which is consistent with their dimeric structures [41,46].…”
Section: 0 Results and Discussionmentioning
confidence: 74%
“…Thus, we can readily generate a connection to a Re(CO) 3 center using metal-mediated Schiff base formation, as shown in Figure 1. We and others have used this reaction to append a wide variety of molecules to the Re(CO) 3 , including aryl rings, fluorescent compounds, peptides and isomerizable groups like azobenzene [44]. These reactions can be carried out using one-pot conditions, and thus for the synthesis of conjugate systems is an attractive way to obtain a variety of structures.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…16 This interest arises from both its notable properties as a non-labile unit with a rigid facial geometry as well as its use as a synthon for a wide variety of functional inorganic complexes. 710 Recently, we have used the Re(CO) 3 moiety as a template to produce isoindoline based chelates that can be considered as half of a phthalocyanine or a hemiporphyrazine (a “semihemiporphyrazine”). 11,12 The limited geometry options and inert nature of this metal unit in both cases prevent larger macrocycles or chelates from forming.…”
mentioning
confidence: 99%